2006
DOI: 10.1242/dev.02475
|View full text |Cite
|
Sign up to set email alerts
|

Specification of theC. elegansMS blastomere by the T-box factor TBX-35

Abstract: In C. elegans, many mesodermal cell types are made by descendants of the progenitor MS, born at the seven-cell stage of embryonic development. Descendants of MS contribute to body wall muscle and to the posterior half of the pharynx. We have previously shown that MS is specified by the activity of the divergent MED-1,2 GATA factors. We report that the MED-1,2 target gene tbx-35, which encodes a T-box transcription factor, specifies the MS fate. Embryos homozygous for a putative tbx-35-null mutation fail to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(88 citation statements)
references
References 58 publications
(101 reference statements)
3
85
0
Order By: Relevance
“…Loss of med-1,2 leads to a highly expressive loss of MS-derived tissues, whereas loss of tbx-35 has a less expressive MS phenotype, especially at lower temperatures (Broitman-Maduro et al, 2006;Maduro et al, 2001) (this work), suggesting that an additional factor contributes to MS specification downstream of MED-1,2 (Broitman- Maduro et al, 2006). From embryonic transcriptome analyses (Baugh et al, 2005;Baugh et al, 2003), we identified Y80D3A.3 as a candidate early MS lineage gene.…”
Section: Identification Of Ceh-51 a Putative Nk-2 Class Homeodomain mentioning
confidence: 65%
See 4 more Smart Citations
“…Loss of med-1,2 leads to a highly expressive loss of MS-derived tissues, whereas loss of tbx-35 has a less expressive MS phenotype, especially at lower temperatures (Broitman-Maduro et al, 2006;Maduro et al, 2001) (this work), suggesting that an additional factor contributes to MS specification downstream of MED-1,2 (Broitman- Maduro et al, 2006). From embryonic transcriptome analyses (Baugh et al, 2005;Baugh et al, 2003), we identified Y80D3A.3 as a candidate early MS lineage gene.…”
Section: Identification Of Ceh-51 a Putative Nk-2 Class Homeodomain mentioning
confidence: 65%
“…3I,J), in which additional MS-like cells are made from the AB and C lineages, respectively (Mello et al, 1992). We have previously found that tbx-35 is still expressed in MS in a pop-1(RNAi) background (Broitman-Maduro et al, 2006), even though in this background MS adopts an E-like fate (Lin et al, 1995). Unexpectedly, most pop-1(RNAi) embryos expressed ceh-51 in both the MS and E lineages (Fig.…”
Section: Ceh-51 Is Expressed In the Early Ms Lineage Downstream Of Tbmentioning
confidence: 83%
See 3 more Smart Citations